Strategi Komunikasi Internal dalam Meningkatkan Motivasi Kerja Guru Sekolah Dasar GMIM IV Tomohon di Era Pandemi Covid-19 - Jeremia Engelita Wakas; Berdinata Massang; Juanda Manullang (Jurnal Manajemen Pendidikan Kristen, 2021)
Internal communication is the key to the sustainability of an organization. Educational Institutions such as schools capable to maintain quality, even in the middle of the Covid-19 Pandemic. Quality and grade are largely determined by the work motivation of teachers in the school. This research will examine the implementation of internal communication at GMIM IV Tomohon Elementary School in motivating teacher’s performance so it will remain productive, creative, and innovative in providing teaching and assistance to students, even during the Covid-19 pandemic. The purpose of this study to determine and understand the implementation of internal communication in increasing the work motivation of teachers at GMIM IV Tomohon Elementary School. This research used is a qualitative approach method with data collection techniques through in-depth interviews with three informants selected by purposive technique. The results showed that the implementation of internal communication at the Tomohon was able to increase teacher’s work motivation even during the Covid-19 pandemic. The researcher found various communication strategies employed by the principal to create effective vertical and horizontal communication. Group communication and interpersonal communication neither formally and informally can create an atmosphere of mutual assistance in the constraints of work and are open to receive input and suggestions that can increase the motivation of teachers' work.